Acute renal infarction resulting from fibromuscular dysplasia: a case report - Saarinen, Harri Juhani (J Med Case Rep, 2016)
BACKGROUND: Acute abdominal pain is one of the most frequent complaints evaluated at emergency departments. Approximately 25 % of abdominal pain patients discharged from emergency departments are diagnosed with undifferentiated abdominal pain. One possible reason for acute abdominal pain is renal infarction. Diagnosis is difficult and often late. CASE PRESENTATION: A white, 33-year-old, previously healthy Finnish man came to our emergency department because of acute abdominal pain. After evaluation and follow-up he was discharged the next day with a diagnosis of undifferentiated abdominal pain. He returned a day later and was diagnosed with renal infarction. Appropriate therapy was initiated in the nephrology ward. Further tests confirmed a diagnosis of renal infarction as a result of fibromuscular dysplasia. He recovered well and was discharged on the tenth day of hospitalization. His renal function was normal. CONCLUSIONS: Renal infarction is rare and should be considered if a patient with intense flank pain has no sign of urolithiasis or pyelonephritis. Contrast-enhanced computer tomography and assay of lactate dehydrogenase are recommended. The optimal treatment is still uncertain. Every patient discharged with undifferentiated abdominal pain should be given clear instructions as to when it is necessary to return to the emergency department.